Pengaruh Kecerdasan Spiritual, Emosional, Intelektual, dan Sosial terhadap Sikap Etis Mahasiswa se-Pulau Lombok - Lalu Takdir Jumaidi; Bambang Bambang; Iman Waskito (Valid: Jurnal Ilmiah, 2022)
Abstract Initiating from the increasing moral hazard occurred, this study aims to examine the effect of spiritual, emotional, intellectual and social intelligence on the ethical attitudes of accounting students. Approach used is quantitative, data analysis used SPSS. The results showed that spiritual and emisional intelligence showed the positive significant influence on ethical behavior of students. Spritual intelegence showed highest level, next is emotional intelligence. This condition shows that spiritual and emotional intelligence have a very strategic position, which can be used as "the basis for curriculum. Intellectual intelligence shows no significant effect on students' ethical attitudes. Likewise with the results of the analysis of social intelligence, This condition because the results of intellectual and social intelligence influenced with spiritual and social intelegense. This condition shows that the education sector plays an important role in continue, especially spiritual and emotional intelligence. The position of gender analysis shows that women are more sensitive to the absorption of the four intelligences in influencing students' ethical attitudes. The results of the "simultaneous" test show that all intelligences have a significant effect on students' ethical attitudes, this condition shows that all intelligences have a strategic function in influencing students' ethical attitudes, if they get attention for strengthening "proportionately and comprehensively"